Preferensi Masyarakat terhadap Tanaman Identitas di Jalur Hijau Tepi Jalan Kota Yogyakarta - Winahyu, Fauziyya Puji; Nasrullah, Nizar; Mas'ud, Zainal Alim (http://arl-faperta.ipb.ac.id/, 2024)
Philosophical and native plants have ecological, aesthetic, and air pollution tolerant functions, and have historical value as constituents of Green Open Spaces (GOS). Plants in the green belt of the Imaginary Line of Yogyakarta are different from other green belt plants, because there are special features. the preferences of the Yogyakarta City community are carried out to choose the right plants, so as to create a good ecosystem on the green belt of Yogyakarta City roads. The purpose of this study was to identify plants to recommendations from people's preferences in choosing green belt plants in the City of Yogyakarta. the research method for selecting respondents used the Slovin method and in-depth interviews with cultural experts from the Yogyakarta Palace, and further tested using the Spearman correlation test. The results showed that of the 33 philosophical and native plants, the physiological characteristics of the plants had a percentage of 8.9%, namely Ficus benjamina L. as a philosophical plant and Chrysopyllum cainito L. 14.6% as a native plant. Visual plant characteristics that have a score of 7 are Murraya paniculata (L.) Jack and Aegle marmelos (L.) Corrêa.